The enlightenment of China's cultural soft power development on Ukraine - Chenlin, Chen (Економіка природокористування і сталий розвиток, 2018)
Cultural soft power is the overall influence and competitiveness of a country's culture. Enhancing the soft power of national culture has become a major strategic issue of each country all over the world. As the world’s second largest economy, the development of cultural industry and the promotion of Chinese culture has always been regarded as an important task, which has made good achievements in the development of China’s cultural soft power. Especially, in recent years, China's leaders have paid high attention to cultural soft power, which has produced cultural influence and attraction to a certain level internationally, and created a beautiful image of China at the same time. This paper makes a systematic analysis on the effect of the development of China's cultural soft power. By combining with the reality of the development of Ukraine's cultural soft power, this paper tries to put forward the way and strategies to develop Ukraine's cultural soft power, to improve policies and regulations, and to implement innovative development of Ukraine's culture on the basis of studying the development measures and beneficial experience of China's cultural soft power. In this way, Ukraine's cultural industry will be stronger and larger, and then, the system of Ukraine’s culture dissemination to foreign countries will be established.